Procedure time and patient perception for ceramic endocrowns or partial coverage ceramic restorations: a double-blind randomized clinical trial - Morimoto, Susana; Fraga, Reinaldo Macedo; Tedesco, Tamara Kerber; Ozcan, Mutlu; Sampaio, Flavia Benali Werneck Rebello; Moreira, Maria Stella Nunes Araújo; Neres Santiago, Anuar Sadat; Raggio, Dainela Procida (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Objetive: This study aimed to compare procedure time and patient discomfort and satisfaction between endocrowns or partial coverage ceramic restorations with fiber post and filling (PCCR+Post). Materials and Methods: A double-blind RCT was carried out according to eligibility criteria: 1) Endodontic treatment; 2) Molars or premolars; 3) Minimum of one cusp with 3-mm thick; 4) Dental antagonists; 5) Supragingival margins; 6) Good oral hygiene; and 7) Minimum of 18 years. Patients were allocated to two groups: Endocrown or PCCR+Post. Each session was timed; discomfort and satisfaction were assessed. Poisson regression analysis and two-way repeated-measures analysis of variance were performed. Results: Forty patients were selected (20 per group). 90% and 82.5% of participants in the PCCR+Post and Endocrown group, respectively, reported little or no discomfort. There was no association between the explanatory variables and the discomfort reported by patients. The level of satisfaction was 100%. Procedure time in the Endocrown (129.7 min±29.78) was similar to PCCR+Post (134.1 min±29.64). Endocrown and PCCR+Post had similar procedure time and patient perception, however, endocrowns allow less clinical steps. Conclusions: Endocrown and PCCR+Post had similar procedure time and patient perception, however, endocrowns allow less clinical steps.